2019
DOI: 10.1007/s13534-019-00133-9
|View full text |Cite
|
Sign up to set email alerts
|

The state of the art of osseointegration for limb prosthesis

Abstract: Osseointegration (OI) is the direct attachment of bone onto a titanium implant. Recently, the term is used to describe "transdermal" implants that allow an external prosthesis to be connected directly to the skeleton. This technology eliminates the challenges of conventional socket-based prostheses, such as skin breakdown and poor fit, which are common in patients with major extremity amputations. Osseointegration patients demonstrate encouraging improvements in quality of life and function. Patients report im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…Prompt integration of implants into host tissue is crucial for the success of prosthesis implantation in orthopedics [ 63 ]. Distinct osseointegration levels were obtained from implants with various coating systems ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prompt integration of implants into host tissue is crucial for the success of prosthesis implantation in orthopedics [ 63 ]. Distinct osseointegration levels were obtained from implants with various coating systems ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term maintenance of the bone-anchored prostheses is challenging due to the risk of mechanical failures and deep infections ( Li and Fellander-Tsai 2021 ). Previous efforts were mainly focused on improving the osseointegration efficiency by the modification of implant surface morphology, changing of implant materials, or improving surgical methods ( Overmann and Forsberg 2020 ). Our 3D finite element analysis revealed that the two maximal stress areas in the screw-type implant system located proximally to the BIC and the connecting rod to external prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 15% of cases in which amputation is indicated, advances in surgical techniques and prosthetic fabrication have led to increased patient satisfaction and acceptance related to improved function and cosmetics. Recently, prosthetic fixation using osteointegration fixation of a metal stem inserted into the medullary cavity has been shown to be especially successful in patients with high femoral amputations 59,60 . Use of this technique obviates the need for using uncomfortable, ill‐fitting sockets.…”
Section: Managementmentioning
confidence: 99%
“…Recently, prosthetic fixation using osteointegration fixation of a metal stem inserted into the medullary has been shown to be especially successful in patients with high femoral amputations. 59,60 Use of this technique obviates the need for using uncomfortable, ill-fitting sockets.…”
Section: Amputationmentioning
confidence: 99%